[Educational Instutions and Their Activities in Islamicjerusalem During Ottoman Period] Sultan II. Abdülhamid'in Konuğu İran Şehzâdesi Hisamüssaltana'nın "Sefernâme-i Mekke" Adlı Eserinde Beytülmakdis Ziyareti (1297-98/1880-81). (2017) - TURAY, Esra DOĞAN
No abstract available